An optimal spectrum-efficient routing protocol for multi-hop 802.11s networks. (2017) - Ba-Hutair, Mohammed N.; Saad, Mohamed
Routing in multi-hop wireless networks is a vital aspect to sustain acceptable performance. Standard routing schemes, such as ad-hoc on-demand vector routing (AODV) and dynamic source routing (DSR), use the number of hops from source to destination as the routing metric without paying attention to the physical layer properties of the wireless links. This paper, however, presents a new routing protocol for finding the path with maximum end-to-end spectral efficiency in real-world IEEE 802.11s networks. In contrast to previous work, our protocol fully considers the physical layer characteristics of the wireless channel, the interaction between network layer route computation and medium access control (MAC) contention resolution, in addition to all necessary information gathering and exchange performed by the wireless nodes. Furthermore, we provide a full NS-2 simulation comparison between spectrum-efficient routing and standard routing protocols using various performance metrics such as end-to-end data rate, delay, packet loss and overhead time.